COVID 19 and Taiwan’s Medical Aid to Honduras: The Last Latin American Frontier for the Republic 2020-2021 - Aswin Ariyanto Azis; Jeffaya Amadeo Basen (AIBPM Publisher, 2022)
Republic of China (Taiwan) has a long history of foreign aid policy/programs towards Honduras, one of their most consistent and strategic allies in the Central American region. As shifts in Taiwan’s foreign policy gradually increased participation of civil actors and number of development projects in Honduras, the arrival of COVID-19 pandemic brought changes to the said aid programs. As a result, Taiwan’s foreign aid program to Honduras changed from development projects to the transfer of medical equipment; masks, ventilators, thermal imager, and test kits from Taiwan to Honduras. As per objective of foreign aid in Taiwan’s white paper on foreign aid policy, foreign aid is utilized to ensure closeness with Taiwan’s diplomatic allies, including Honduras. This study hence is aimed to extensively explore the effect of the COVID-19 pandemic on Taiwan’s aid to Honduras through qualitative-descriptive means. In the end, uncertainty lingers around the future of Taiwan’s diplomatic relations with Honduras and subsequent foreign aid policy limited by their inability to produce vaccines, perhaps showing the weakness of Taiwan’s previous shift to value-based aid approaches in times of crisis compared to material aid. Keywords: Covid 19, Foreign/Medical Aid, Honduras, Taiwan, Vaccines